'All the Musics Which Computers Make Possible':1 Questions of genre at the Prix Ars Electronica. Issue 1 (April 2016) - Haworth, Christopher
Abstract : This article explores the workings of genre in experimental electronic musics. Predominantly sociological in orientation, it has three main foci. First, it addresses practitioners' and theorists' resistances to the concept of genre in experimental musics. Drawing on recent developments in genre theory, it discusses the problems of agency, mediation and scale that any discussion of genre calls forth, pitting them alongside theories that emphasise genre's necessity and inevitability in communication. The second section examines the politics of genre as they play out in practice, focusing on the Prix Ars Electronica festival and the controversy that ensued from the decision to change the name of the Computer Music category in 1999. The analysis focuses on issues of institutional mediation, historicity, genre emergence and the politics of labelling as they come into view when two broad spheres – electroacoustic art music and 'popular' electronic music – are brought into the same field together in competition. The third section deepens the analysis of Ars Electronica by zooming in on one of the represented genres, microsound, to examine how it is shaped and negotiated in practice. Using digital methods tools developed in the context of Actor-Network Theory, I present a view of the genre as fundamentally promiscuous, overlapping liberally with adjacent genres. Fusing Derrida's principle of 'participation over belonging' with ANT's insistence on the agency of 'non-human actors' in social assemblages, the map provides a means to analyse the genre through its mediations – through the varied industries, institutions and social networks that support and maintain it.